2020
DOI: 10.1101/2020.09.09.288910
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of multi-day rTMS and cardiorespiratory fitness on working memory and local GABA concentration

Abstract: Working memory (WM) refers to the capacity to temporarily retain and manipulate finite amounts of information; a critical process in complex behaviours such as reasoning, comprehension, and learning. This cognitive function is supported by a parietal-prefrontal network and linked to the activity of key brain neurotransmitters, such as gamma-aminobutyric acid (GABA). Impairments in WM are seen in a range of psychiatric and neurological disorders, and there are currently no effective methods of remediating WM de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 95 publications
1
0
0
Order By: Relevance
“…Considered in the context of the present study, these outcomes indicate that the effects of cTBS on GABA concentration may be regionally specific, with considerable variability observed across the distinct cortical regions targeted in past studies. This perspective is also supported by a recent study which reported differential effects of multi-day rTMS on GABA concentration between parietal cortex and pre-supplementary motor area targets (Hendrikse et al, 2020b). Overall, our findings challenge the consistency of cTBS-induced effects on GABA outside of the motor system.…”
Section: Discussionsupporting
confidence: 64%
“…Considered in the context of the present study, these outcomes indicate that the effects of cTBS on GABA concentration may be regionally specific, with considerable variability observed across the distinct cortical regions targeted in past studies. This perspective is also supported by a recent study which reported differential effects of multi-day rTMS on GABA concentration between parietal cortex and pre-supplementary motor area targets (Hendrikse et al, 2020b). Overall, our findings challenge the consistency of cTBS-induced effects on GABA outside of the motor system.…”
Section: Discussionsupporting
confidence: 64%